1976
DOI: 10.1007/bf02532989
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of 30 species of yeast

Abstract: The detailed composition of cellular lipid of more than 23 species of yeast has been determined quantitatively by thinchrography on quartz rods, a method previously used for estimating cellular lipids of seven species of yeast. That data was fortified by neutral and phospholipid quantitations on 30 species of yeast cells. Most of the test organisms contained 7-15% total lipid and 3-6% total phospholipid per dry cell weight, except for the extremely high accumulation of triglycerides in two species of Lipomyces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
1
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 13 publications
10
53
1
1
Order By: Relevance
“…It was similar to that reported for C. albicans (19,32,45) and Saccharomyces cerevisiae (13 Table 3). Naftifine and tolnaftate, at 10 and 100 p.M, respectively, inhibited sterol biosynthesis by 70% and caused a 10-fold accumulation of squalene.…”
Section: Resultssupporting
confidence: 90%
“…It was similar to that reported for C. albicans (19,32,45) and Saccharomyces cerevisiae (13 Table 3). Naftifine and tolnaftate, at 10 and 100 p.M, respectively, inhibited sterol biosynthesis by 70% and caused a 10-fold accumulation of squalene.…”
Section: Resultssupporting
confidence: 90%
“…ITOH and KANEKO (14) reported that pyro-PA was detected in Kb. apiculata, but this phospholipid was not found in the same strain in the following study (15). In this study, pyro-PA was not found in 3 strains of Kb.…”
Section: And Discussioncontrasting
confidence: 55%
“…ITOH and KANEKO (13) reported that pyrophosphatidic acid [P,P-bis-(1,2-diacyl-sn-glycero-3)-pyrophosphate] (pyro-PA), was first found in the cellular lipid of Cryptococcus neoformans (13), and was also found in 2 strains of Cryptococcus, 2 of Rhodotorula, and 1 of Trichosporon (14,15). This paper describes the distribution of pyro-PA in ascomycetous and basidiomycetous yeast species (241 strains belonging to 167 species of 43 genera), and suggests that the presence of pyro-PA in yeast species is significant in yeast taxonomy.…”
mentioning
confidence: 99%
“…For Candida albicans, there are reports on the lipid composition of the plasma membrane and cell wall (Marriott, 1975), variation in lipid composition associated with dimorphism (Ghannoum et al, 1986), and the effect of antifungal agents on lipids (Singh et al, 1979). Total lipid content ranges from 7% to 32% in various species of Candida (Kaneko et al, 1976). Phosphatidylcholine (PC), p hosphatidylethanolamine (PE), p hosp hatidylserine (PS) and phosphatidylinositol (PI) represent the major phospholipids, while triglycerides, free sterols, esterified sterols and free fatty acids are the major neutral lipids (Henry et al, 1981;Kaneko et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Total lipid content ranges from 7% to 32% in various species of Candida (Kaneko et al, 1976). Phosphatidylcholine (PC), p hosphatidylethanolamine (PE), p hosp hatidylserine (PS) and phosphatidylinositol (PI) represent the major phospholipids, while triglycerides, free sterols, esterified sterols and free fatty acids are the major neutral lipids (Henry et al, 1981;Kaneko et al, 1976). Although C. albicans lipids have been studied in detail, information on lipid biosynthesis is meagre and variation in lipid content among different strains has not been studied.…”
Section: Introductionmentioning
confidence: 99%